2014
DOI: 10.1021/la500331u
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Surfactants and Colloidal Latexes in Nonpolar Solvents Studied Using Contrast-Variation Small-Angle Neutron Scattering

Abstract: The interaction between deuterium-labeled Aerosol OT surfactant (AOT-D 34 ) and stericallystabilized poly(methyl methacrylate) (PMMA) latex particles dispersed in nonpolar solvents has been studied using contrast-variation small-angle neutron scattering (CV-SANS). The electrophoretic mobilities (µ) of the latexes have been measured by phase-analysis light scattering, * To whom correspondence should be addressed † School of Chemistry, University of Bristol, Cantock's Close, Bristol, BS8 1TS, United Kingdom

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
54
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(59 citation statements)
references
References 52 publications
4
54
1
Order By: Relevance
“…A fit to these data gives an SLD for the latexes of ρ n =(1.1 ± 0.1) × 10 −6Å−2 . This is consistent with recent experimental measurements of the SLD of a similar PMMA latex [74] and the values used in other studies [58,69,70]. The scattering of the latexes has been analyzed using a model for core-shell spheres under different contrast conditions, and this confirmed that the scattering length density is higher in the center of the latex than in the stabilizer shell [73,82,83].…”
Section: Nm Diameter Latexessupporting
confidence: 90%
See 3 more Smart Citations
“…A fit to these data gives an SLD for the latexes of ρ n =(1.1 ± 0.1) × 10 −6Å−2 . This is consistent with recent experimental measurements of the SLD of a similar PMMA latex [74] and the values used in other studies [58,69,70]. The scattering of the latexes has been analyzed using a model for core-shell spheres under different contrast conditions, and this confirmed that the scattering length density is higher in the center of the latex than in the stabilizer shell [73,82,83].…”
Section: Nm Diameter Latexessupporting
confidence: 90%
“…Fluorescence energy-transfer studies have shown that small molecules can distribute throughout the cores [103][104][105]. Other small molecules, such as residual hexane solvent [106] or surfactant charging agents [74,76], can also be distributed throughout the cores of the latexes. Given that molecules are able to partition throughout the volume of the latexes, the core polymers could be highly porous and therefore significantly less dense than the pure polymer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, x-ray scattering studies [23] showed a fascinating phase behavior of Wigner crystals, including a body-centered-cubic (bcc) phase at low concentration, and a solid-solid transition to a face-centered-cubic (fcc) phase at higher densities [15][16][17][18]24,25]. It is also possible to induce charge on particles in nonaqueous solvents through the addition of charge control agents [21,[26][27][28]. However, in this case, there is strong coupling between the charge on the particle surface and the ions in solution.…”
mentioning
confidence: 99%